A Prospective Observational Study on Ocular Manifestations of Sickle Cell Hemoglobinopathies - Pradhan, Ipsita; Dash, Rutayani; Dash, Krusnasis (Student’s Journal of Health Research Africa, 2024)
Background: Sickle cell disease (SCD) is a genetic hemoglobinopathy described by abnormal hemoglobin S, leading to systemic complications due to vaso-occlusion and hemolysis. Ocular manifestations, particularly proliferative sickle retinopathy (PSR), can result in significant visual impairment if not detected and treated early. The study assessed the prevalence, types, and risk factors associated with ocular manifestations in individuals with SCD and to explore the relationship between disease severity and ocular complications. Methods: Included were 205 individuals with SCD diagnoses, of which 74 showed signs and symptoms related to the eyes. Patients received thorough evaluations by ophthalmologists, which included fundus examinations, slit-lamp biomicroscopy, and fluorescein angiography. SPSS version 23.0 was used for the statistical analysis. P-values less than 0.05 were regarded as significant. Results: Ocular manifestations were observed in 36.1% of patients (n=74). The most common findings were proliferative sickle retinopathy (43.2%) and non-proliferative sickle retinopathy (28.4%). Patients with severe SCD were significantly more likely to have ocular manifestations (51.4%) compared to those with mild disease (16.2%) (p = 0.002). The mean duration of SCD was longer in patients with ocular involvement (14.4 vs. 10.8 years, p = 0.032). Visual impairment was present in 27.0% of patients with ocular manifestations. Conclusion: A substantial proportion of patients with SCD develop ocular complications, with proliferative sickle retinopathy being the most common. The severity and duration of SCD are associated with an increased risk of ocular manifestations, emphasizing the need for regular ophthalmological evaluations. Recommendations: Routine ophthalmological screening should be integrated into the management of patients with SCD, particularly for those with severe disease or longer disease duration. Early detection and treatment of ocular manifestations may help prevent vision loss.